Formulasi Sediaan Masker Pelembab Ekstrak Etanol Kulit Pisang Mas (Musa acuminata L.) - Debi Meilani; Cucu Arum Dwi Cahya; Aminah Syarifuddin; Regina Elyanda Tampubolon (Yayasan Penelitian dan Inovasi Sumatera, 2022)
Background: Moisturizing cosmetics are care cosmetics that aim to maintain structure and function from various influences. One of the cosmetic preparations for facial skin care is a facial mask. Objective: The research is aimed at formulating and evaluating the Mas banana peel extract moisturizing mask formulation formula. Method: Formulation is carried out by adding the extract to the moisturizing preparation formula and evaluating it, including pH, dry time, spreadability, stickiness, moisture and irritation. Results: The results showed that the Mas banana peel ethanol extract mask preparation obtained had a pH of 6.1 - 6.5, dry time of 16.9 - 25.0 minutes, spreadability of 4.98 - 33.49 cm2, and very adhesive power. firm, average humidity 31.5 -52.9%, no irritation to the skin. Conclusion: A moisturizing mask from the ethanol extract of mas banana peel is effective as a skin moisturizer, equivalent to cosmetics containing 2% glycerin, does not cause skin irritation, has a standard cosmetic pH, and has good spreadability and adhesion